Academic Entrepreneurialism and Private Higher Education in Europe (Chapter 6) - Kwiek, Marek (My University, 2013)
In this chapter we will focus on basic ideas and key concepts functioning in research on academic entrepreneurialism. The reference point here will be public institutions (the original focus of reflection both in Europe and the USA) and private institutions (under-researched from this particular analytical perspective both in Europe and in the USA). Apart from the discussion of the individual core elements of the “entrepreneurial university”, there will be discussions intended to see the difference in the sense of the term of academic entrepreneurialism related to the public and private sectors across Europe. An extended analysis will be devoted to differences in how academic entrepreneurialism operates in both sectors in practice. This chapter is structured as follows: following this introduction, part two discusses the phenomenon of increasing diversification of the financial base and new sources of revenues of entrepreneurial universities, focusing on the fact that over the past two decades in OECD countries, increases in funding for higher education and research occurred in all sources other than the core, traditional and guaranteed government support (whose role has been decreasing gradually for several years). Therefore, the principle of competition plays a key role in entrepreneurial educational institutions: even state funding is becoming more competitive than ever before but, most importantly, all other revenue sources are becoming almost fully competition-based. The third part examines the role of Burton Clark's “strengthened steering core” in entrepreneurial private institutions, and in the fourth part another feature of the entrepreneurial university is addressed, that is the “expanded developmental periphery” (i.e. new scientific and administrative units that attract to universities an increasing proportion of external funding). The fifth part on the “stimulated academic heartland” shows that academic entrepreneurialism can be found across all academic disciplines, while the sixth part discusses the critical role of emergent, institution-wide culture of entrepreneurialism. Finally, findings on the entrepreneurial nature of private institutions in the comparative context of public institutions to which the category has been traditionally referred are presented: paradoxically, the private sector in Europe (based on empirical research on Portuguese, Polish, Spanish and Italian private institutions) turns out to be far less entrepreneurial than could be expected. Conclusions are less paradoxical in the case of Central and Eastern Europe: small islands of academic entrepreneurialism – viewed by Burton Clark, Michael Shattock and Gareth Williams as institutions (or their parts) taking academic and financial risk in their research, in search of prestige and external funding – can be found almost exclusively in the public sector. The private sector, focused on teaching rather than research in an overwhelming number of institutions, funded in 90-95 percent by tuition fees paid by students, is not a sector where academic entrepreneurialism in a sense adopted so far in the research literature can be found. While traditional (research-based) academic entrepreneurialism is found across Western European systems, private institutions in Central and Eastern Europe tends to exhibit entrepreneurial features only in teaching-oriented activities.
Keywords: academic entrepreneurship; academic entreprenerialism; entrepreneurial universities; Burton R. Clark; entrepreneurship; third stream funding; non-core funding; non-state income; risk-taking; Mike Shattock; Gareth Williams; EUEREK; European Universities for Entrepreneurship; entrepreneurship education; independent private; European universities; private higher education; private sector; privatization; higher education; Daniel C. Levy; private sector growth; case studies; Central Europe